THE MOST SUITABLE WORDS AND STRUCTURES - Omar, Sumaya; Ezzat , Azza (Humanities Journal of University of Zakho, 2025)
The linguistic usage in the Holy Qur’an exhibits a unique distinctiveness، characterized by its precise selection of words over their synonyms and its syntactic structures that harmonize seamlessly with their contextual settings in an unparalleled and remarkable manner. In this study، we have selected three verses that exemplify different patterns of variation in meaning. These include variations in closely related words، such as massa (مَسَّ) and lamsa (لَمَسَ); variations in syntactic structures، such as ulū qurbā (أُولُو قُرْبَى)، ulū al-qurbā (أُولُو الْقُرْبَى)، and dhawī al-qurbā (ذَوِي الْقُرْبَى); as well as differences in the use of prepositions، such as anzalnā ʿalayk (أَنْزَلْنَا عَلَيْكَ) versus anzalnā ilayk (أَنْزَلْنَا إِلَيْكَ). Additionally، we examine variations in verbal forms، distinguishing between active and passive constructions، as seen in ātaynāhum al-kitāb (آتَيْنَاهُمُ الْكِتَابَ) and ūtū al-kitāb (أُوتُوا الْكِتَابَ). Such distinctions are abundant in the Qur’anic text، each serving a distinct rhetorical and semantic function.